Analisis Isi Lambung Ikan Sumatra (Puntius hexazona) Di Lingkungan Perairan FPK Universitas Riau dan Hulu Sungai Sibam Pekanbaru - Nicken, Nicken; Windarti, Windarti; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractSumatran fish (Puntius hexazona) is a type of freshwater fish that inhabits the waters around the Riau University and the upstream of the Sibam River. A study aims to determine the type of food in the stomach of the fish from both areas was conducted in July – September 2019. Sampling was carried out 4 times, once/ 2 weeks. The fish was captured using scoop nets. There were 88 fishes (42 fishes from the upstream of the Sibam River and 46 fishes from the streams in the Riau University), but 4 fishes have empty stomach and they cannot be analyzed. The type of food present in the stomach of fish from both sampling areas were similar. The main food the fish in from the Riau University’s waters was insecta remains (IP 83%), crustacean remains (12% IP) and plant remains (5% IP). While that of the Sibam River was crustacean remains (IP 91%), insecta remains (IP 5%), and rotifers (IP 4%). P. hexazona has viliform teeth, short and firm gill rakers and the length of intestine was 1.2 times of total length. Data obtained indicate that P. hexazona is an omnivorous fish.Keywords: Main Food, Omnivorous Fish, Index of Preponderance, Feeding habit